Programa Ler e Escrever: análise de uma proposta oficial para o tratamento da leitura - Negrão, Thaís Inácio (2012)
This dissertation is situated in the field of teaching and learning the Portuguese language, in the area of studies concerning the Linguistic Education. The research investigates how reading is treated in a education program Ler e Escrever education program of state government of São Paulo, deployed by the State Department of Education of São Paulo, in 2008, to intervene in the teaching of reading and writing offered to elementary school student in order to verify if its proposals in the area of reading, in fact, contribute to the formation of proficient reader. Therefor, it took a qualitative approach, combining exploratory descriptive search-with the documentary, whose primary sources are in the works made public by SEESP. Sought, in this survey, answer the following question: read practices implemented by professor of Elementary cycle I of the State network of São Paulo, under the guidance of the program to read and write, in fact, contribute to the formation of a proficient reader? The study also proposes not only to verify to what extent the theoretical assumptions of the program Read and Write subsidise the work of teaching, but also compare the reading practices used by teachers in elementary school I cycle with those suggested by the program. The proposed theoretical foundations for the development of research lie in an interface between the areas of Psicogênese of written language and Textual Linguistics, favouring the dynamic relationships between theory and practice. The knowledge inherent in the field of history of Brazilian education made it possible to contextualize the origin of the program to read and write and avoid distortions in distorted analyses